ROLE OF ERANDADI TAILA NASYA AND KARNAPURANA IN THE MANAGEMENT OF KARNA NADA - A CLINICAL STUDY - Rakesh Bishnoi; Gulab Chand Pamnani (International Journal of Applied Ayurved Research, 2018)
Tinnitus is perception of sound that was no external source. It can be constant or intermittent and is heard in one ear, both ear (behind the eardrum) or in sensory neural auditory system tinnitus is real neural activity in brain. In Ayurveda it is correlated with Karna Nada which is Vata-Kapha dominant in nature. Aim: To evaluate the effect of proposed Ayurvedic treatment protocol in the patients of tinnitus. Materials and Methods:The studies were conducted in 15 patients of Karna Nada and were treated with Erandadi Taila in form of Nasya and Karnapurana for 1 month. Results: It revealed statistically extremely significant relief in tinnitus. Furthermore, sustained relief was found in follow-up. Conclusion: Ayurvedic treatment protocol is effective in the management of tinnitus.